2013
DOI: 10.1186/1475-2875-12-10
|View full text |Cite
|
Sign up to set email alerts
|

Operational scale entomological intervention for malaria control: strategies, achievements and challenges in Zambia

Abstract: BackgroundWhile consensus on malaria vector control policy and strategy has stimulated unprecedented political-will, backed by international funding organizations and donors, vector control interventions are expansively being implemented based on assumptions with unequaled successes. This manuscript reports on the strategies, achievements and challenges of the past and contemporary malaria vector control efforts in Zambia.Case descriptionAll available information and accessible archived documentary records on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 28 publications
1
55
1
Order By: Relevance
“…in fishing areas [12,22]. Misuses of the ITN, such as use to catch fish and use of nets for animals were also noted (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…in fishing areas [12,22]. Misuses of the ITN, such as use to catch fish and use of nets for animals were also noted (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…In response to the international calls to protect both human health and the environment from DDT through the United Nation Environment Programme (UNEP), Global Environment Facility (GEF) and WHO, Zambia has halted the use of DDT for IRS [30]. In the quest of deploying non insecticide based interventions for a sustainable environment, Larval source management has been integrated in the national Malaria Control Programme [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Countries engage in malaria control [33][34][35][36] and elimination [37] may learn from Bangladeshi experiences. Spatial analytical studies have shown a higher incidence of malaria in areas adjacent to these international borders [26].…”
Section: Spatially Explicit Mathematical Modelsmentioning
confidence: 99%